2014
DOI: 10.1111/iwj.12363
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life psychosocial characteristics in Greek patients with leg ulcers: a case control study

Abstract: Chronic leg ulcers are a public health problem that can have a significant impact on the patient's physical, socioeconomic and psychological status. The aim of this study is to evaluate the quality of life, anxiety and depression, self-esteem and loneliness in patients suffering from leg ulcers. A total of 102 patients were enrolled in the study. The quality of life, anxiety and depression, self-esteem and loneliness of the patient were assessed using the Dermatology Life Quality Index (DLQI), Hospital Anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 16 publications
1
32
0
1
Order By: Relevance
“…A possible explanation could be the fact that it is quite difficult for older family members, who possibly have to contend with their own personal health problems, not only to take care of themselves, but also of another member of the family with leg ulcers that needs extra care and attention. The findings of this study confirm those of previous studies in so far as our patients showed a significant impairment in QoL (mean, 13.29 ± 2.31) . The condition of these patients has a marked impact on their daily activities, social life, physical function, mental, and emotional health status .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A possible explanation could be the fact that it is quite difficult for older family members, who possibly have to contend with their own personal health problems, not only to take care of themselves, but also of another member of the family with leg ulcers that needs extra care and attention. The findings of this study confirm those of previous studies in so far as our patients showed a significant impairment in QoL (mean, 13.29 ± 2.31) . The condition of these patients has a marked impact on their daily activities, social life, physical function, mental, and emotional health status .…”
Section: Discussionsupporting
confidence: 90%
“…Although the effect of leg ulcers on the patient's quality of life (QoL) has been documented, very little is known about the effect on the QoL of family caregivers. Chronic leg ulcers have a major impact on the patient's psychological, socioeconomic, and physical status.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Instruments measuring HRQoL are increasingly being developed for that purpose. Chronic wounds are associated with a considerable loss of physical, emotional and social quality of life . Therefore, assessment of HRQoL in wound care is of great importance in research as well as in routine clinical practice.…”
mentioning
confidence: 99%
“…It is affecting approximately 1% of the general Western European population . High health care cost, significant impact on patients' quality of life and loss of productivity are inherent to this widespread health issue . Chronic foot and leg ulcer was earlier defined as an ‘open sore below the knee anywhere on the leg or foot which takes more than six weeks to heal’ .…”
Section: Introductionmentioning
confidence: 99%